SDM Development Strategy of Doa Sepuh Barbershop Business - Rindi Apridianti; Sabrina Shela Fatimah Zahra; Dwi Epty Hidayaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
Usaha Kecil dan Menengah (UMKM) alre one of the most importalnt palrts of the Indonesialn economy. Usaha Kecil dan Menengah (UMKM) plaly aln importalnt role in the Indonesialn economy becaluse they caln crealte jobs alnd provide results thalt benefit society. UMKM caln operalte three types of businesses to generalte profits: malnufalcturing, tralding alnd service businesses. The diversity of UMKM nalturallly crealtes complex business competition, with alll competing industries/enterprises engalging in valrious competitive alctions alnd competitive responses. The balrbering business is al promising business todaly, especiallly for someone with good skills. Everyone needs al nealt alppealralnce, one of the things thalt must be considered is halir.